Activating KIRs in Chronic Lymphoproliferative Disorder of NK Cells: Protection from Viruses and Disease Induction? - Zambello, Renato; Teramo, Antonella; Barilà, Gregorio; Gattazzo, Cristina; Semenzato, Gianpietro (Frontiers in Immunology, 2014)
Human natural killer (NK) cells are functionally regulated by killer cell immunoglobulin like receptors (KIRs) and their interactions with HLA class I molecules. As KIR expression in a given NK cell is genetically established, KIR repertoire perturbations reflect a dominance of discrete NK-cell subsets as the consequence of adaptation of the NK-cell compartment to exogenous agents, more often represented by virus infection. Although inhibitory interactions between KIR and their cognate HLA class I ligands abrogate effector responses of NK cells, they are also required for the functional education of NK cell. The biology and molecular specificities of the activating KIRs are less well defined, and most interactions with presumed HLA class I ligands are weak. Interestingly, epidemiologic studies link activating KIR genes to resistance against numerous virus infections. Chronic Lymphoproliferative Disorder of NK cells (CLPD-NK) is an indolent NK cell disease characterized by a persistent increase of circulating NK cells (usually exceeding 500 NK cells/mm3). The mechanism through which NK cells are induced to proliferate during CLPD-NK pathogenesis is still a matter of debate. Accumulating data suggest that exogenous agents, in particular viruses, might play a role. The etiology of CLPD-NK however is largely unknown. This is likely due to the fact that not a single, specific agent is responsible of the LGL proliferation, which perhaps represents the expression of an abnormal processing of different foreign antigens, sharing a chronic inflammatory background. Interestingly, proliferating NK cell are typically characterized by expression of a restricted pattern of KIR, which have been demonstrated to be mostly represented by the activating form. This finding indicates that these receptors may be directly involved in the priming of GL proliferation.